Chinese Students' Perception and Expectation of Online and Post-Pandemic Teaching and Learning Approaches in a UK Transnational Program - Caoimhe Clerkin; Taher Hatahet; Maryam Malekigorji; Gavin P. Andrews (MDPI AG, 2022)
A cloud of uncertainty around how to deliver teaching on transnational education programs (TNE) in the new post pandemic era has been created due to little evidence of investigation available. This study for the first time explored the needs and expectations of students (324) enrolled on BSc Pharmaceutical Science and Pharmaceutical Biotechnology degrees at a China UK Joint College, to understand their preferences for the delivery of such programs. Surveys were circulated amongst students to collect qualitative (open questions) and quantitative (Likert-scaling) data around the infrastructure for online learning (internet, IT device, learning platforms and study place) as well as the challenges and expectations of online learning, including student preference towards the delivery of materials, in a post-pandemic era. Focus groups, facilitated by the delivery team, were organized to collect further qualitative data and to explore common themes arising from the surveys and to understand student requirements more thoroughly for a successful TNE program. The data gathered determined that the transition to online learning has been challenging for students, and that they significantly (p < 0.001) prefer a hybrid model of teaching, consisting of a mixture of digital and on-campus activities. For the first time, this study demonstrates strategies to ensure that the needs and expectations of students in a TNE program are reached in post-pandemic era and the quality of teaching and learning are enhanced.